The challenges of the university in the construction of new knowledge, capabilities, and skills. University and prospective of higher education (2023)
Objective: Education, at the university level, faces many challenges, especially with the flattening invasion of globalization and globalization that requires and demands transcendental and significant transformations in its daily work. The university, as an institution of higher education, as is the case of the Universidad de San Carlos de Guatemala (USAC), has a specific mission, which focuses on three central axes: teaching, research, and university extension. These pillars support and guide its openness to new opportunities, to respond to national, regional, and global problems. Originality/contribution: The university must be alert and attentive to this call with a prospective view, without losing sight of the retrospective learnings that can be of help to face future scenarios, especially for youth people, who full of hope, are eager to enter inhospitable paths and at the same time are devoured by the new information and communication technologies. The purpose of this article is to analyze the role of the university in the 21st century, regarding the changes in higher education and the possible new archetype of a university education that demands the insertion of changes. Method: review of a philosophical framework, which covers the mission and vision, as well as the axiological component; an academic framework. Likewise, it consists of an academic reflection that intends to call the attention of the different actors of the academic community, with the intention of establishing spaces for academic dialogues. Strategies/information collection: They consisted of the use of techniques, such as: Textual or content analysis, which made it possible to investigate the different documentary points of view in order to arrive at a reflection. Website analysis, to gather relevant information, given the production of material related to the study.  Documentary review, which made it possible to evaluate the documents to verify their validity and reliability of their content. Open sources and database, which allow to have an approach with the information that interests to analyze to complement the study. Conclusions: it is necessary to review both the design of programs and their development, as well as digital literacy and the transdisciplinary approach. It is essential to have a legal framework that revises the concept of university autonomy, the university's own functions, and university policies, which should be based on transversal axes that are present in all academic programs. In this way, the university is not left in a total obsolescence, since the graduates are those who are inserted into the labor market, both in the private and public sectors.